The Evolution of the White Coat - Tahir, Tayyeb A (Journal of Pakistan Psychiatric Society, 2022)
<div class="page" style="padding: 0px; margin: 1px auto -8px; direction: ltr; width: 992px; height: 1403px; position: relative; overflow: visible; background-clip: content-box; border-image: url(’images/shadow.png’) 9 / 1 / 0 repeat; background-color: white; border: 9px solid transparent;" data-page-number="1" data-loaded="true"> <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 63.5405px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif;">“ <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 70.8733px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif;">Y <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 77.8315px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.926586);">our <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 103.468px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.921762);">pain <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 135.803px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.845339);">is <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 148.916px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.931446);">the <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 173.828px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.92118);">breaking <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 235.983px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.939381);">of <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 252.423px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.931446);">the <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 277.336px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.88578);">shell <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 310.801px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.989193);">that <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 341.908px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.860306);">encloses <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 401.479px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.919338);">your <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 434.572px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.900409);">unders <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 480.252px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif;">t <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 485.607px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.921801);">anding. <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 539.29px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.975801);">It <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 551.875px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.845339);">is <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 564.988px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.931446);">the <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 589.9px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(1.02204);">bit <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 607.739px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif;">t <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 613.144px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.897539);">er <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 629.617px; top: 309.338px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.947943);">potion <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 63.5357px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.890173);">by <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 82.1035px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.92294);">which <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 124.539px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.931446);">the <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 149.274px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.924578);">ph <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 166.113px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.889853);">ysician <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 214.401px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.975529);">within <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 259.311px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.899767);">you <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 286.512px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.881387);">heals <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 324.545px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.919338);">your <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 357.46px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.858345);">sick <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 384.906px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.901302);">self <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 407.415px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.862377);">. <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 414.247px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.901703);">Theref <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 457.436px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.904921);">ore, <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 486.443px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.948796);">trus <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 512.61px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(1.01001);">t <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 520.817px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.931446);">the <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 545.552px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.924578);">ph <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 562.391px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.889853);">ysician <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 610.678px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.90876);">and <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 639.011px; top: 327.574px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.933589);">drink <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 63.5322px; top: 345.81px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.873659);">his <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 84.6725px; top: 345.81px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.907541);">remedy <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 137.771px; top: 345.81px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.918797);">in <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 152.425px; top: 345.81px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.883154);">silenc <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 189.917px; top: 345.81px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.844479);">e <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 200.135px; top: 345.81px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.90876);">and <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 228.104px; top: 345.81px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.983154);">tranquility <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 297.387px; top: 345.81px; font-size: 16.6667px; font-family: sans-serif;">. <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 300.375px; top: 345.81px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(1.05635);">” <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 313.322px; top: 364.045px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.898733);">-Khalil <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; left: 357.557px; top: 364.045px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.90452);">Gibran <div class="endOfContent" style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: default; transform-origin: 0% 0%; display: block; inset: 1403px 0px 0px; z-index: -1; user-select: none;"> <div class="page" style="padding: 0px; margin: 1px auto -8px; direction: ltr; width: 992px; height: 1403px; position: relative; overflow: visible; background-clip: content-box; border-image: url(’images/shadow.png’) 9 / 1 / 0 repeat; background-color: white; border: 9px solid transparent;" data-page-number="2" data-loaded="true"> <div class="canvasWrapper" style="padding: 0px; margin: 0px; overflow: hidden; color: #000000; font-family: Arial; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; width: 992px; height: 1403px;"> <div class="textLayer" style="padding: 0px; margin: 0px; position: absolute; inset: 0px; overflow: hidden; opacity: 0.2; line-height: 1; color: #000000; font-family: Arial; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; width: 992px; height: 1403px;">